Making cities work : prospects and policies for urban America - Inman, Robert P. (Princeton University Press, 2009)
Making Cities Work brings together leading writers and scholars on urban America to offer critical perspectives on how to sustain prosperous, livable cities in today's fast-evolving economy. Successful cities provide jobs, quality schools, safe and clean neighborhoods, effective transportation, and welcoming spaces for all residents. But cities must be managed well if they are to remain attractive places to work, relax, and raise a family; otherwise residents, firms, and workers will leave and the social and economic advantages of city living will be lost. Drawing on cutting-edge research in the social sciences, the contributors explore optimal ways to manage the modern city and propose solutions to today's most pressing urban problems. Topics include the urban economy, transportation, housing and open space, immigration, race, the impacts of poverty on children, education, crime, and financing and managing services. The contributors show how to make cities work for diverse urban constituencies, and why we still need cities despite the many challenges they pose. Making Cities Work brings the latest findings in urban economics to policymakers, researchers, and students, as well as anyone interested in urban affairs. In addition to the editor, the contributors are David Card, Philip J. Cook, Janet Currie, Edward L. Glaeser, Joseph Gyourko, Richard J. Murnane, Witold Rybczynski, Kenneth A. Small, and Jacob L. Vigdor.